A Comparative Study to Evaluate the Role of Alpha Tocopherol in Pregnancy induced Hypertension (Medical Forum Monthly, 2024)
Objective: To assess the role of alpha tocopherol in Pregnancy Induced Hypertension (PIH) by comparing pregnancy induced hypertensive patients on routine anti-hypertensive measures with pregnancy induced hypertensive patients on alpha tocopherol plus routine antihypertensive measures.Study Design: Retrospective Randomizing Study.Place and Duration of Study: This study was conducted at the Department of Pharmacology and Therapeutics, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from April 2004 to Sept. 2004.Materials and Methods: Two groups each comprising of 25 pregnancy induced hypertensive females, age ranging from 18-40 years were studied in this study. Changes in systolic and diastolic blood pressure were assessed from 24-28 weeks of pregnancy and were followed at every 15 days till the time of delivery in Control Group-I (G-I) and Test Group-II (G-II).Results: On day-0 systolic blood pressure on average showed higher value in G-II compared to G-I. On day 30, 60 and day final, the mean systolic blood pressure showed lower values in G-II although the difference was found statistically insignificant. When diastolic blood pressure studied, it showed on the average same readings for G-I and G-II on day-0. On day 30, day 60 and day final, it also showed statistically insignificant difference between G-I and G-II with higher mean diastolic blood pressure in G-I.Conclusion Alpha tocopherol exerted better effect on systolic and diastolic blood pressure in test group when compared with control group.